2011
DOI: 10.1038/nnano.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

A single synthetic small molecule that generates force against a load

Abstract: Some biomolecules are able to generate directional forces by rectifying random thermal motions. This allows these molecular machines to perform mechanical tasks such as intracellular cargo transport or muscle contraction in plants and animals. Although some artificial molecular machines have been synthesized and used collectively to perform mechanical tasks, so far there have been no direct measurements of mechanical processes at the single-molecule level. Here we report measurements of the mechanical work per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 31 publications
1
106
0
Order By: Relevance
“…The technique has been widely used to determine equilibrium thermodynamic parameters by mechanically driving probed molecules out of equilibrium at various loading rates (16,(20)(21)(22)(23)(24). To date, there have been very few investigations reported on wholly synthetic small molecules (31,(40)(41)(42)(43)(44), mainly because of the difficulty of preparing appropriate molecules that can be interfaced with single-molecule force spectroscopy techniques, but also because the size of the molecules implies that the rupture events occur at very small distances, in the range of 1 nm. Here we have probed donor-acceptor oligorotaxane foldamers, synthetic prototypes of molecular switches, by AFM-based dynamic force spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique has been widely used to determine equilibrium thermodynamic parameters by mechanically driving probed molecules out of equilibrium at various loading rates (16,(20)(21)(22)(23)(24). To date, there have been very few investigations reported on wholly synthetic small molecules (31,(40)(41)(42)(43)(44), mainly because of the difficulty of preparing appropriate molecules that can be interfaced with single-molecule force spectroscopy techniques, but also because the size of the molecules implies that the rupture events occur at very small distances, in the range of 1 nm. Here we have probed donor-acceptor oligorotaxane foldamers, synthetic prototypes of molecular switches, by AFM-based dynamic force spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The oligorotaxanes were grafted onto gold-coated silicon substrates using our previously established method (31) to obtain a sparse regime of the molecule of interest. The substrates were dipped for 1 h in a solution of the oligorotaxane (2 × 10 −8 mol) containing 90 mol % of dodecyl disulfide in Me 2 CO at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the nonequilibrium work is a fluctuating quantity of interest in small systems such as single molecules subjected to the time-dependent forces of optical tweezers or atomic force microscopy [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Stoddart et al demonstrated the first solid-state rotaxane switch system directed toward molecular electronic devices and opened the door for the rotaxane-based molecular machine creating macroscopic work. 6 The actual observation of the switching behavior of rotaxane in solid state has been recently achieved.…”
mentioning
confidence: 99%